1996
DOI: 10.1099/13500872-142-3-525
|View full text |Cite
|
Sign up to set email alerts
|

How do Highly Branched (Colonial) Mutants of Fusarium Graminearum A3/5 arise during Quorn® Myco-Protein Fermentations?

Abstract: Furthermore, the margins of heterokaryotic colonies generally contained nuclei from only one of the parental homokaryons, indicating imperfect nuclear mixing within the mycelium. These observations suggest that recessive, colonial mutants may appear during Quoma myco-protein production following shear-induced separation of hyphal fragments which contain a sufficiently high ratio of colonial : wild-type nuclei for the colonial phenotype to be expressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Decreased branching is a rarely reported as a mutant phenotype in filamentous fungi (Watters and Griffiths, 2001), though increased branching mutants are frequently identified (Bocking et al, 1999;Lauter et al, 1998;Propheta et al, 2001;Sone and Griffiths, 1999;Steele and Trinci, 1977;Wiebe et al, 1996), In the present work we describe the identification and characterization of two abnormal hyphal branch mutants: the hypobranching ahbA1 and hyperbranching ahbB1.…”
Section: Introductionmentioning
confidence: 69%
“…Decreased branching is a rarely reported as a mutant phenotype in filamentous fungi (Watters and Griffiths, 2001), though increased branching mutants are frequently identified (Bocking et al, 1999;Lauter et al, 1998;Propheta et al, 2001;Sone and Griffiths, 1999;Steele and Trinci, 1977;Wiebe et al, 1996), In the present work we describe the identification and characterization of two abnormal hyphal branch mutants: the hypobranching ahbA1 and hyperbranching ahbB1.…”
Section: Introductionmentioning
confidence: 69%
“…For several complementary nit-based heterokaryons of Fusarium graminearum, even a strong selective pressure was insufficient to maintain heterokaryons in a 'balanced' condition (Wiebe et al, 1996). In Colletotrichum gloeosporioides f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Wiebe et al (1992aWiebe et al ( , 1996b have previously shown that when heterokaryons are formed between highly branched mutants in this manner, the macroconidia (monokaryotic) formed by the heterokaryon will have the morphology of the two highly branched mutants from which the heterokaryon was formed. All crosses were made on modified Vogel's medium containing only glutamine as the nitrogen source (Wiebe et al, 1992a).…”
Section: Heterokaryon Formationmentioning
confidence: 99%